Decrease of total activity with time at long distances from a nuclear accident or explosion - Dolejs, Josef (Radiation and environmental biophysics, 2005)
Two data groups were analyzed: (1) the exposure rate in the former Czechoslovakia after the Chernobyl accident in 1986, and (2) the decrease of beta activity of an atmospheric fallout sample taken in Bratislava during 24 h on 30 May 1965. Both quantities decreased with the first power of time. This pattern of decrease is explained by applying the same mathematical formalism as is also used to describe the decrease in postnatal mortality with age. Following this formalism, the decrease of total activity with the first power of time could be seen as a consequence of a log-normal distribution of decay constants in the fallout. This differs slightly from earlier results that show the total activity decreasing with a power of 1.2 immediately after the nuclear explosion.
Keywords: časové faktory; dávka záření; Radiation Dosage; Time Factors; Czechoslovakia; Radioactive Fallout; radioaktivní znečišťující látky; Half-Life; černobylská havárie; Chernobyl Nuclear Accident; poločas; monitorování radiace; Radioactive Pollutants; Československo; radioaktivní spad; Radiation Monitoring